Identification of Motile Aeromonas Strains with the MicroScan WalkAway System in Conjunction with the Combo Negative Type 1S Panels - Vivas, J. (American Society for Microbiology, 2000)
This study was performed to compare the MicroScan WalkAway automated identification system in conjunction with the new MicroScan Combo Negative type 1S panels with conventional biochemical methods for identifying 85 environmental, clinical, and reference strains of eight Aeromonas species.